2022
DOI: 10.48048/asi.2023.254659
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Value Co-Creation on Student Loyalty, Satisfaction, and University Image: A Case Study of an Anonymous Rajabhat University

Abstract: A university’s primary duty is to provide essential skills to help students work well after graduation. The quality of a university’s students depends on the university’s value proposition. In the past, Rajabhat University’s value proposition may not have been sufficiently constructed with co-creation. Although co-creation may now be more emphasized, it is still insufficient. The primary objective of this study is to use a composite model based on the structural equation model of students’ experiences to asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 61 publications
3
8
0
Order By: Relevance
“…However, the more significant the customer's value cocreation behavior level, the greater the customer's loyalty to the company (Baehaqi et al, 2023). Prior studies found that value co-creation has a positive relationship with student loyalty in the context of HEI (Jhantasana, 2022); mobile legend game players (Arissaputra et al, 2023); and Sampoerna Retail Community (Baehaqi et al, 2023). The study postulates that the increase of student value co-creation is correlated with increased student loyalty.…”
Section: Student Value Co-creation and Student Loyaltymentioning
confidence: 87%
See 4 more Smart Citations
“…However, the more significant the customer's value cocreation behavior level, the greater the customer's loyalty to the company (Baehaqi et al, 2023). Prior studies found that value co-creation has a positive relationship with student loyalty in the context of HEI (Jhantasana, 2022); mobile legend game players (Arissaputra et al, 2023); and Sampoerna Retail Community (Baehaqi et al, 2023). The study postulates that the increase of student value co-creation is correlated with increased student loyalty.…”
Section: Student Value Co-creation and Student Loyaltymentioning
confidence: 87%
“…In this manner, the final results of numerous previous studies fail to demonstrate the advantageous result of significant co-creation of value (Ranjan & Read, 2016). According to Jhantasana (2022); Sholehuddin et al (2023), incorporation of the value co-creation model is necessary within the framework of the thirdorder build. In contrast, the constructs of satisfaction and image are derived from secondorder models, which are built upon three-stage and two-stage aspect designs, respectively.…”
Section: Student Value Co-creationmentioning
confidence: 98%
See 3 more Smart Citations